ANALISIS FINANSIAL USAHA PENANGKAPAN RAJUNGAN (Portunus pelagicus) DENGAN PENGGUNAAN UMPAN YANG BERBEDA DI KABUPATEN KONAWE SELATAN, SULAWESI TENGGARA - Muh Aksa Azis; Rizky Ayu Lestari; Suhartin.T (Program Studi Ilmu Perikanan, Fakultas Ilmu dan Teknologi Hayati, Universitas Teknologi Sumbawa, 2024)
Fishing is an economic activity influenced by various production factors with the primary goal of generating profit. The success of a fishing operation is measured by the amount of profit obtained. Fishermen in South Konawe use folding traps to catch blue swimming crabs (Portunus pelagicus). Blue swimming crabs are a fishery commodity with high market value, both in local markets and as an export commodity. The objectives of this study include analyzing the technical aspects of folding traps in South Konawe waters, analyzing the income, costs, and profits of the fishing operation, and assessing the financial feasibility of the blue swimming crab fishing operation using folding traps in South Konawe waters with different baits. This research was conducted from August 2020 to September 2020 in the Tinanggea District. The method used in this study is a survey method, which involves field observation, direct observation, and data collection on-site. The data analysis model used is business feasibility analysis with several indicators, including NPV, B/C Ratio, IRR, and payback period. The results show that folding traps fall under the trap category. Each year, operational costs vary, but overall, they are higher than fixed costs. The use of tembang fish bait generates the highest revenue, which is sufficient to cover operational costs. Therefore, the business is considered feasible and profitable based on the analysis of NPV, IRR, and B/C Ratio, with a moderate category of capital return. On the other hand, the use of trash fish bait results in losses because the revenue generated is insufficient to cover the costs. Consequently, the blue swimming crab fishing operation using trash fish bait is considered unfeasible and unprofitable..